Comparison of Microstructure and Hardness of Sintered Carbon Fiber and Carbon Nanotubes Reinforced Copper Matrix - Noraini Binti Esa, Noraini (Universiti Teknologi Petronas, 2009)
Rapid growth of advance electronics device in electronics industry has its limitation in overheating problem. The solution for this limitation is by introducing the heat sinking material which has excellent properties such as higher thermal conductivity, hardness and strength. This report presents research of final year project, the Comparison of Microstructure and Hardness of Sintered Carbon Fiber and Carbon Nanotubes (CNTs) Reinforced Copper Matrix. Carbon nanotubes and carbon fibers were reinforced in the range of 2.5% to 10% of volume fraction. The main objective of the project is to develop the samples of composites using a powder metallurgy (PM) process. Two mixtures of copper and carbon nanotubes and copper and carbon fibers were blended and compacted into metallic die under pressure of 490MPa. The compacted samples were sintered at 900°C for one and half hour in argon environment. This research focuses on the microstructures of sintered samples to determine the hardness and bonding between carbon nanotubes-copper and carbon fiber-copper. The results show that density of the composites is decreased after sintering process and the composites experience volume expansion due to grain growth which can be seen in the microstructure images result from optical microscopy and Scanning Electron Microscope. Hardness of the carbon fiber reinforced copper matrix is improved from the range of 61.32HV up 126.7HV but decreased for carbon nanotubes reinforced copper matrix due high volume of voids and porosity area on the microstructure surface